1984
DOI: 10.1021/j150663a032
|View full text |Cite
|
Sign up to set email alerts
|

Cryochemical studies. Part 8. Electron spin resonance spectra of dioxygen complexes of Group IB metal atoms

Abstract: Adducts of group IB metal atoms to molecular oxygen (Cu02, Ag02, and Au02) have been prepared in a rotating cryostat at 77 K and isolated in adamantane. Electron spin resonance spectra at 10 and 77 K indicate that most of the unpaired spin population in these complexes resides in a tt* orbital on the two oxygen nuclei with low but measurable unpaired s spin population on the metal atom. ESR spectra of mono(dioxygen) complexes enriched in 170 suggest that Cu02 has end-on bonding with magnetically and spatially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 0 publications
2
37
0
Order By: Relevance
“…The asymmetric local minimum of the lowest state, 'A", resulting from the SCF C,-symmetry optimization, leads to an energy slightly above that of the symmetric equilibrium geometry. This result is in agreement with some of the experimental data [20], but remains contrary to Illas et al's [23] theoretical findings.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The asymmetric local minimum of the lowest state, 'A", resulting from the SCF C,-symmetry optimization, leads to an energy slightly above that of the symmetric equilibrium geometry. This result is in agreement with some of the experimental data [20], but remains contrary to Illas et al's [23] theoretical findings.…”
Section: Resultssupporting
confidence: 78%
“…From these data, the presence of a nonsymmetric A,-0-0 species was inferred. Further experimental investigations by means of ESR techniques have also been reported where the spectroscopic data indicate a symmetric structure of silver dioxide possessing a side-on bonding with equivalent oxygen atoms [20]. More recently, Kasai and Jones [21], also based on matrix isolation ESR studies, have concluded that A , 0 2 presents a bent, end-on structure, thus again supporting the appearance of an asymmetric structure.…”
Section: Introductionmentioning
confidence: 88%
“…[1][2][3][4][5][6] The observed vibrational frequencies provide the key evidence. Figure 3 shows a spectrum taken at 532 nm detachment wavelength ͑fluence: 40 mJ/cm 2 ͒ to enhance the spectral resolution for the 1.5 eV band.…”
mentioning
confidence: 87%
“…The interaction between Cu atom and O 2 is an important process and has been studied both in low temperature matrix [1][2][3][4][5][6] and in the gas phase. [7][8][9] Ground state Cu atom forms a molecular complex with O 2 , which takes on a bent CuOO ͑C s ͒ structure.…”
mentioning
confidence: 99%
“…As said in the Introduction, EPR experiments [29][30][31] show two magnetically inequivalent oxygen atoms and this had been taken as an indication that the end-on Cs structure is the ground state. CASPT2 calculations by Roos et al 37 indicate that the gas-phase ground state is the side-on 2 A2 state but because of the small energy difference between the two species, the 2 A'' Cs structure, which has a large dipole moment, becomes the groundstate in rare-gas matrices.…”
Section: Tables 1-5 Herementioning
confidence: 97%